Efficiency of noise reduction by a road speed bump - MAKAREWICZ, Rufin; KOKOWSKI, Piotr (Archives of Acoustics, 2007)
The vehicle noise from a road with a bump consists of the deceleration noise, bump noise, and acceleration noise. The bump is modeled by the Dirac delta function. The linear density of sound energy (in Joules per meter) is used for the calculation of sound energies, ec and e, emitted by a vehicle on a road without- and with a bump, respectively. The ratio η=(ec-e)/e defines the efficiency of noise reduction by a speed bump. To determine η, four measurements of the sound exposure level have to be done. The example of such measurements and calculation of η is given.